SMAD4-induced knockdown of the antisense long noncoding RNA BRE-AS contributes to granulosa cell apoptosis - Wang Yao; Xing Du; Jinbi Zhang; Yang Wang; Miaomiao Wang; Zengxiang Pan; Qifa Li (Elsevier, 2021)
Antisense long noncoding RNAs (AS-lncRNAs), a sub-class of lncRNAs, are transcribed in the opposite direction from their overlapping protein-coding genes and are implicated in various physiological and pathological processes. However, their role in female reproduction remains largely unknown. Here, we report that BRE-AS, an AS-lncRNA transcript from intron 10 of the protein-coding gene BRE, is involved in granulosa cell (GC) apoptosis. Based on our previous RNA sequencing data, we identified 28 AS-lncRNAs as important in the initiation of porcine follicular atresia, with BRE-AS showing the most significant upregulation in early atretic follicles. In this study, gain- and loss-of-function assays demonstrated that BRE-AS induces early apoptosis in GCs. Mechanistically, BRE-AS acts in cis to suppress the expression of BRE, an anti-apoptotic factor, via direct interaction with the pre-mRNA transcript of the latter, inducing increased GC apoptosis. Notably, we also found that BRE-AS was upregulated in SMAD4-silenced GCs. SMAD4 was identified as a transcriptional repressor of BRE-AS because it inhibits BRE-AS expression and BRE-AS-mediated GC apoptosis. In conclusion, we not only identified a novel AS-lncRNA related to the early apoptosis of GCs and initiation of follicular atresia but also described a novel regulatory pathway, SMAD4/BRE-AS/BRE, coordinating GC function and female fertility.